The Body for beginners - Cavallaro, Dani (Orient Longman, 1998)
The documentary comic books of the For Beginners series deal with complex and serious subjects. They attempt to untimidate and uncomplicate the great ideas and work of great thinkers. The movements and concepts dealt with are placed in their historical, political and intellectual contexts. The books are painstakingly researched, humourouly written and enlivened with classic comic-strip illustrations, photographs, paintings, etc. The range of subjects covered is truly vast and varied?Malcom X and the New Age guru Castenanda, Shakespeare and Foucault, Jewish Holocaust and Arab and Israel, Structuralism and Biology.